Hybrid Grid Partition and Rought Set Methods for Generating Fuzzy Rules in Supply Chain - Marsoit, Patrisius Michaud Felix; Pernadate, Park Vrançoisee; Jérôme, Jesca Fell (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
Supply chain management in today's dynamic and complex business environment demands innovative approaches to decision support. This research introduces a novel hybrid framework that combines grid partition, rough set methods, and fuzzy logic to generate adaptive fuzzy rules tailored to supply chain data. By integrating these techniques, the study provides a comprehensive decision support system capable of addressing the intricacies and uncertainties prevalent in supply chain operations. A numerical example illustrates the practical application of this framework in optimizing inventory management within an e-commerce supply chain. The results showcase the effectiveness of the adaptive fuzzy rules in minimizing stockouts, reducing excess inventory, and optimizing inventory costs. Additionally, the study emphasizes the importance of balancing rule quality and complexity using a tunable parameter, offering flexibility for rule customization. The interpretability of the generated fuzzy rules further enhances their practical utility, enabling domain experts to comprehend and adjust decision criteria. This research not only contributes to advancing decision support systems in supply chain management but also lays the groundwork for future exploration of real-world data integration, adaptability to dynamic environments, and scalability challenges, thus promising significant enhancements in supply chain performance and resilience.